2018
DOI: 10.1186/s12885-018-4468-5
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like 4 promotes osteosarcoma cell proliferation and migration and stimulates osteoclastogenesis

Abstract: BackgroundOsteosarcoma is the most common primary bone cancer in children and young adults. It is highly aggressive and patients that present with metastasis have a poor prognosis. Angiopoietin-like 4 (ANGPTL4) drives the progression and metastasis of many solid tumours, but has not been described in osteosarcoma tissue. ANGPTL4 also enhances osteoclast activity, which is required for osteosarcoma growth in bone. We therefore investigated the expression and function of ANGPTL4 in human osteosarcoma tissue and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 64 publications
4
40
1
Order By: Relevance
“…Previous studies demonstrated that ANGPTL4 was associated with a variety types of cancers such as osteosarcoma, 16 gastric cancer, 17 renal cell carcinoma, 18 non-small cell lung cancer, 19 and cervical cancer, 20 and played pivotal roles in tumor growth, proliferation and metastasis. 21 ANGPTL4 was identified as a factor of lipid metabolism and angiogenesis which could be regulated by the nuclear hormone receptors PPARs, hypoxic conditions, fasting, and transforming growth factor β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that ANGPTL4 was associated with a variety types of cancers such as osteosarcoma, 16 gastric cancer, 17 renal cell carcinoma, 18 non-small cell lung cancer, 19 and cervical cancer, 20 and played pivotal roles in tumor growth, proliferation and metastasis. 21 ANGPTL4 was identified as a factor of lipid metabolism and angiogenesis which could be regulated by the nuclear hormone receptors PPARs, hypoxic conditions, fasting, and transforming growth factor β.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that ANGPTL4 promotes the migration and differentiation of endothelial cell, leading to the formation of new blood vessels. 14,15 The expression of ANGPTL4 was increased in several solid tumors such as osteosarcoma, 16 gastric cancer, 17 renal cell carcinoma, 18 non-small cell lung cancer, 19 cervical cancer 20 and so on compared with corresponding paracancerous tissues. ANGPTL4 was identified as pro-tumorigenic protein, including stimulating tumor cell growth and proliferation, promoting tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…HIF‐1α functions importantly in promoting tumor metastasis and proliferation . We investigated the function of HIF‐1α in circPIP5K1A/miR‐600‐mediated NSCLC cell proliferation and migration.…”
Section: Resultsmentioning
confidence: 99%
“…HIF-1α functions importantly in promoting tumor metastasis and proliferation. [22][23][24] We investigated the function of HIF-1α in circPIP5K1A/miR-600-mediated NSCLC cell proliferation and migration. Bifluorescein reporter detection showed that cotransfection of miR-600 mimics and reporter plasmids (including the HIF-1α 3′-UTR) decreased luciferase activity, whereas cotransfection with miR-600 mimics and mutated vectors verified that there was no obvious effect on luciferase activity.…”
Section: The Mir-600 Targets the Hif-1α Gene 3′-utrmentioning
confidence: 99%
“…Knockdown of ANGPTL4 reportedly suppresses adenylate energy charge elevation, thus delaying EMT [26]. Upregulation of ANGPTL4 is associated with a poor prognosis of cancers and promotes tumor cell proliferation and migration, including OS cells [27,28]. STC1, as well as STC2, was originally identi ed as a calcium/phosphate-regulating hormone.…”
Section: Discussionmentioning
confidence: 99%